ANTIBACTERIAL AND CYTOTOXIC ACTIVITIES OF ACACIA AROMA EXTRACTS - Mattana, Claudia M.; Satorres, Sara E.; Escobar, Franco; Sabini, Carola; Sabini, Liliana; Alcaráz, María Fusco; Lucía E. (Emirates Journal of Food and Agriculture, 2017)
Acacia aroma, native plant from San Luis, Argentina, is used commonly like antiseptic and healing of wounds. The present study was conducted to investigate the in vitro antibacterial activity of extracts of A. aroma and its toxicity on Vero cell. The bacterial strains used were Staphylococcus aureus ATCC 43300, S. aureus ATCC 35556, Listeria monocytogenes CLIP 74910 and L. monocytogenes CLIP 74904. The minimal inhibitory concentration (MICs) and minimal bactericidal concentration (CBMs) was determined and tested at concentration ranges from 5000 to 78µg/mL. On the other hand, the cytotoxic activity on Vero cells was assayed by MTT method. The MIC values of EE and HAE against S. aureus was 156µg/mL and 625µg/mL respectively. MBC values were one or two fold higher than the corresponding MIC values in both extracts. Listeria strains studied gave MICs and MBCs values of 78µg/mL and 312µg/mLl respectively for EE, while HAE showed less antibacterial activity against this strain (MIC=1250µg/mL and MBC=5000µg/mL). The CC50 was 658µg/mL for EE and 1020µg/mL for HAE. The extracts of A. aroma tested in vitro showed inhibitory activity against Staphylococcus and Listeria. These results allow validating the external use of this plant.